Prophetic Leadership of Manahijussadat Islamic Boarding School in Realizing a Sustainable Islamic Education Ecosystem in Banten Province - Falahudin, Iwan; Anshori, Irfan; Wasehudin; Setiaji, Heri; Maulana, Hasan (The Magister of Islamic Education IAIN Pontianak, 2026)
The sustainability of Islamic education in Islamic boarding schools faces serious challenges amid social change, increasing demands for institutional professionalism, and the dynamics of religious values. This study aims to examine the practice of prophetic leadership at Pondok Pesantren Manahijussadat and its role in building a sustainable Islamic education ecosystem in Banten Province. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed thematically to obtain a comprehensive understanding of leadership patterns and the process of internalizing prophetic values. The findings indicate that prophetic leadership at Pondok Pesantren Manahijussadat is implemented through role modeling, deliberation, and service, and is grounded in the values of humanization, liberation, and transcendence. These values are not only embodied in the leader's personal conduct but are also institutionalized within the pesantren's systems, organizational culture, and governance. Prophetic leadership plays a crucial role in integrating various components of the educational ecosystem, strengthening cadre regeneration, and maintaining the continuity of values and social relations with the surrounding community. This study contributes to the literature on Islamic educational leadership by positioning prophetic leadership as a value-based foundation and an institutional mechanism for achieving sustainable Islamic education